2006
DOI: 10.1007/s11255-006-9031-7
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoid tumor arising in a horseshoe kidney

Abstract: Carcinoid tumors are common neoplasms developing in gastrointestinal and respiratory tract. They are rarely found in the kidney. To date, approximately 40 cases of primary renal carcinoid tumors have been reported, with less of a third of them occurring within a horseshoe kidney. These cases appear to have a better prognosis, even in the presence of distant metastases, compared to those arising in normal kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 11 publications
(14 reference statements)
0
18
1
Order By: Relevance
“…Investigations included a computed tomography (CT) scan of her accurate pathological diagnosis, the incidence of reported primary renal carcinoids is on the rise. A total of 88 cases of this rare cancer (based on case reports and case series) have been published, 1,[3][4][5][6][7][8][9] with the largest multicentre series involving 21 patients. 10 To our knowledge, we present the first published case of renal carcinoid tumour presenting with an IVC thrombus.…”
Section: Case Reportmentioning
confidence: 99%
“…Investigations included a computed tomography (CT) scan of her accurate pathological diagnosis, the incidence of reported primary renal carcinoids is on the rise. A total of 88 cases of this rare cancer (based on case reports and case series) have been published, 1,[3][4][5][6][7][8][9] with the largest multicentre series involving 21 patients. 10 To our knowledge, we present the first published case of renal carcinoid tumour presenting with an IVC thrombus.…”
Section: Case Reportmentioning
confidence: 99%
“…The fused tissue is the isthmus and it prevents the kidneys from ascending and rotating due to the resistance it exerts as it reaches the inferior mesenteric artery. HSK may be associated with other urinary tract and extrarenal abnormalities, including stenosis of the ureteropelvic junction, double pelvis, abnormalities of the urinary bladder, supernumerary kidneys with horseshoe elements, undescended testis and hypospadias, septate vagina; skeletal, cardiovascular, gastrointestinal and central nervous system malformations, chromosomal abnormalities (including Patau and Gardner syndromes, Down and Turner syndromes) [1][2][3][4][5][6]. Moreover, HSK has been found even more frequently in autopsy examinations of children and infants, suggesting the high risk of mortality in young age, probably due to severe associated organ and/or chromosomal abnormalities [1].…”
Section: Discussionmentioning
confidence: 99%
“…HSK can be complicated by the formation of kidney stones, hydronephrosis (due to stenosis of the ureteropelvic junction, malrotation and/or malposition of the kidneys and ureters, obstruction by stones), urinary tract infections and tumors (Wilms' tumorusually in the isthmus, transitional cell carcinoma, oncocytoma, carcinoid tumors) [1][2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 There is an interesting, and as yet unexplained, association of renal carcinoids with horseshoe kidneys. 10,15,16 In their review of the literature, McVey and associates 13 demonstrated that carcinoids were 60 -80 times more likely to develop in horseshoe kidneys than in normally developed kidneys. The prognosis is difficult to predict, and some patients with metastatic disease may have a prolonged clinical course.…”
Section: Case 1: Well-differentiated Neuroendocrine Carcinoma Of the mentioning
confidence: 99%